2015
DOI: 10.1016/j.enpol.2015.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the long-term economic benefits of European electricity system integration

Abstract: This paper analyses a set of model-based decarbonization scenarios in order to quantify the long-term economic benefits that arise from an increasing integration of the pan-European electricity system. It thereby focuses on the interplay between transmission infrastructure and renewable generation capacity expansion. We confirm earlier findings that, on aggregate, pan-European transmission capacity expansion constitutes a no-regret option for integrating increasing shares of variable renewables in mitigation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…On the European level, most energy scenarios are characterized by ESMs where each country is represented by either a single or only a few modeled regions [11,12]. Therefore, spatial data are aggregated, or in other words, the total power generation and consumption of a defined region are concentrated at one point while neglecting intra-regional power flows.…”
Section: Motivationmentioning
confidence: 99%
“…On the European level, most energy scenarios are characterized by ESMs where each country is represented by either a single or only a few modeled regions [11,12]. Therefore, spatial data are aggregated, or in other words, the total power generation and consumption of a defined region are concentrated at one point while neglecting intra-regional power flows.…”
Section: Motivationmentioning
confidence: 99%
“…Coats, 2013). Modelling studies have revealed that -given the substantial uncertainties -an increased investment into photovoltaic energy in Southern Europe could be part of a cost-efficient European energy transition (Schmid and Knopf, 2013;Knopf et al, 2013). At the same time, economic analysis suggests that increased stimulus investments into European debt crises ridden states could reduce unemployment and relieve the deep recession (Koo, 2011;Andersen et al, 2012).…”
Section: The Politics Of Nonactionmentioning
confidence: 99%
“…The traditional landscape with large and steady central power production units based on coal, nuclear, oil, and gas is increasingly being replaced by more decentralized and rapidly maturing power generation units such as wind and solar plants . This shift is increasingly putting pressure on various authorities and traditional market systems as they have to integrate these naturally fluctuating and widely dispersed energy sources into national and international main grid constellations that require grid upgrades to be constantly aligned with the interconnector needs …”
Section: Introductionmentioning
confidence: 99%
“…With neighbouring countries continuing their own build‐out of VRE sources, to a large extent correlating in production patterns with Danish VRE and thus putting further pressure on the price per megawatt hour (MWh) from VRE in general, these planned grid build‐outs are not expected to effectively mitigate the challenges facing the entire VRE investment ecosystem . Thus, highlighting the relevance of this study and identifying and exploring conceptual alternatives and potentials for VRE investors to sustain value of VRE‐producing assets via transformative technologies and multivalue business models, such integrative energy solutions—catalysing the green transition and sealing the gap between VRE capacity and VRE generation—may very well prove to be “the next big thing” on an international scale as well …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation